Pengaruh Kualitas Layanan Mobile Banking Terhadap Kepuasan Nasabah Bank Syariah Indonesia (Studi Kasus Pada Pegawai Al-Fityan Boarding School Bogor) - Lestari, Devi; Wibowo, Finantyo Eddy; Muti, Ahmad (Universitas Labuhanbatu, 2023)
Information technology and adult telecommunications are so fast that patterns of life and interhuman communication are affected, which information technology is know as the internet. Mobile Banking includes a service provided by banks to their clients to facilitate their transactions. You don’t have to come to the bank, because it’s a lot of good news. Wherever they can still act so they don’t interfere with the schedule. This study aims to determine the effect of Mobile Banking service quality on customer satisfaction at Bank Syariah Indonesia (Case Study on Employees of Al- Fityan Boarding School Bogor). The method used is a combination of quantitative and qualitative methods (Mix Methods) with a Sequential Explanatory model. The data source for this research is Al-Fityan Boarding School Bogor employees who use the Mobile Banking application. By using data collection techniques through interviews and questionnaires. Data analysis techniques used in this research are data quality tests, namely validity and reliability tests, classic assumption tests, namely normality tests and linearity tests, hypothesis testing, namely simple regression tests, correlation tests, coefficient of determination tests and t tests. After going through the quantitative procedures followed by qualitative procedures.This study obtained the results that the Quality of Mobile Banking Services had an effect on Customer Satisfaction as evidenced by the correlation test which obtained the results between the X and Y variables which were 0.686 > 0.05, so Ha was accepted and Ho was rejected. Which means that service quality has a positive effect on customer satisfaction. Then based on the tests that have been carried out with the coefficient of determination is 0.471 or around 47.1% This means that the effect of the independent variable on the dependent variable is 47.1% Meanwhile , the remaining 52.9% is explained by other variables not examined in this study.Based on the results of this study, the independent variable (Service Quality) has a significant effect on the dependent variable (Customer Satisfaction).